Outcomes of TP53‐mutated AML with evolving frontline therapies: Impact of allogeneic stem cell transplantation on survival. Issue 7 (30th March 2022) - Badar, Talha; Atallah, Ehab; Shallis, Rory M.; Goldberg, Aaron D.; Patel, Anand; Abaza, Yasmin; Bewersdorf, Jan P.; Saliba, Antoine N.; Correia, Guilherme Sacchi De Camargo; Murthy, Guru; Duvall, Adam; Burkart, Madelyn; et al.
Abstract :